2021
DOI: 10.1002/ijgo.13973
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of CO2 laser treatment in postmenopausal women with vulvovaginal atrophy: A meta‐analysis

Abstract: Objective: To explore the efficacy of CO 2 laser treatment in postmenopausal women with vulvovaginal atrophy.Method: PubMed, Embase, Cochrane Library and Web of Science were searched to June 9, 2020. Prospective studies on the efficacy of CO 2 laser treatment were included. Two researchers independently reviewed articles and extracted data.Heterogeneity test was conducted for each outcome indicator. Sensitivity analysis was performed in all models.Results: Twelve articles including 459 participants were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The increase in life expectancy of women necessitates further scientific study and the development of appropriate therapies for the relief of GSM symptoms that can be used for all women [ 20 , 21 , 22 ]. GSM is a factor that impacts the quality of life and affects a broad age group [ 1 , 3 , 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in life expectancy of women necessitates further scientific study and the development of appropriate therapies for the relief of GSM symptoms that can be used for all women [ 20 , 21 , 22 ]. GSM is a factor that impacts the quality of life and affects a broad age group [ 1 , 3 , 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of increasing the population size for further long-term evaluations of the parameters should not be ruled out. Although the principles of laser therapy are established in medicine, especially in dermatology, this study provides new and unprecedented therapeutic perspectives regarding the application of laser technology in gynecology because it is free from side effects and possible endometrial repercussions caused by using hormones [ 21 , 22 ]. Currently, a better understanding of the duration of the effects of this method and its long-term consequences and the functions of these processes at the epithelial, cellular, and nuclear levels is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis of observational studies suggested laser therapy is likely to be effective in improvement of GSM, which was in accordance with our meta-analysis of 6 RCTs with relatively consistent study designs. In our analysis, all included studies applied the laser regimen of 2 to 3 sessions with an interval of 4 to 6 weeks .…”
Section: Discussionmentioning
confidence: 99%
“…Juliet, Cutera 360°sequential pulses, 1 cm apart; 2 passes 1st is ablative, 2nd is coagulative [40] Hybrid Er:YAG 2940 nm/ 1470 nm diode Diva, Sciton Automated tx, choose 90°,190°, or 360°NA lidocaine gel) may be applied to the vulva for 10 min before external genital treatment with fractional devices and affords adequate pain control.…”
Section: Preoperative Physical Examination and Testingmentioning
confidence: 99%
“…The settings on the device are provided by each manufacturer. [30][31][32][33][34][35][36][37][38][39][40] In general, the fluence (for microablative CO 2 laser) is in the low range of approximately 250-300 mJ/cm 2 and the spacing of the microbeams is approximately 1 mm apart. The handpiece is inserted fully into the vault.…”
Section: Vulvovaginal Protocolmentioning
confidence: 99%